First reported case of fulminant TB with progression of infection from lungs to the genitourinary region - Adzic-Vukicevic, Tatjana (2017)
Although tuberculosis (TB) is a curable disease, it continues to be one of the leading infections associated with death in the world. Extra-pulmonary TB (EPTB) occurs in approximately 10% of the total cases, presenting with lymph nodes, pleura, bone and genitourinary tract as the most common locations. Genitourinary tuberculosis, the second most common EPTB, is very difficult to diagnose unless there is a high index of suspicion. Isolated TB orchitis or prostatitis without clinical evidence of renal involvement is a rare entity among genitourinary tuberculosis. We presented the first reported case of TB prostatitis and orchitis associated with pulmonary TB and the presence of an acute massive caseous pneumonia in an immunocompetent man. Despite the anti-TB therapy, the patient presented a rapid progression of disease and deterioration of general conditions taking to death, which occurred four days after TB treatment had started. Disseminated TB is a relatively uncommon cause of acute massive caseous pneumonia; however, there should always be suspicion of the disease, since it is a potentially treatable cause. This rare case supports the assertion that TB should be considered as an important differential diagnosis of genitourinary tumors irrespective of evidence of active TB elsewhere in the body.